Manufacture of a cooling path of an advanced design for the combustion chamber of a liquid rocket engine using additive technologies - Сергій Вікторович Аджамський; Ганна Андріївна Кононенко; Ростислав Вячеславович Подольський (Авіаційно-космічна техніка та технологія, 2021)
The creation of complex structural elements of aircraft using additive technologies is promising and is widely used since such elements have many design and technological advantages over the collection of individual finished parts. However, it requires the solution of many scientific and technical problems to obtain products of high accuracy and density, develop a technological process, work out modes, and sometimes develop a new design of products. When the angles of inclination of the inclined surfaces are more than 45 °, in the manufacture of parts using the technology of selective laser melting, special conditions arise that cause some restrictions. Since the tracks that form the bottom layer (down-skin) of the inclined surface largely lie not on the previous layer of the metal part, but on the powder surrounding the part, the melt pool "falls through" into the powder, the melt pool breaks through, disrupting the track continuity. As a consequence, the bottom layer (down-skin) of the formed inclined at an angle of more than 45 °, and the horizontal surface has a high roughness. We studied samples of elements of the cooling path with an improved design (the shape of the channels in the form of parallelograms with an acute angle of 45 °) and with the original design (the shape of the channels in the form of rectangles) with a change in the angle of inclination of the channels relative to the Z-axis. According to the results of visual-optical analysis and determination of the down-skin roughness, it was found that at tilt angles to the Z-axis ≥75 ° with the original design of the channels, the transverse surface of the channel may not even form or have significant deviations from the specified geometry, and with the improved design of the channels, the roughness of the down-skin is only slightly increased. From the analysis of the change in roughness at tilt angles of the channels relative to the Z-axis in the range of 40…60 °, it was found that samples with an improved channel design have similar roughness values (5…6.5 μm), and for samples with an original channel design, the roughness changed significantly (6…22 μm). A model was developed and a combustion chamber cooling path was manufactured with channels of an improved design and an angle of inclination of the channels of 74 °. The possibility of manufacturing a combustion chamber cooling duct with an angle of inclination of the channels relative to the Z-axis using the technology of selective laser melting at a high metal density and low surface roughness of the inner channels is shown.